Are Your Eggs Broken? A Study of Chromosomal Breakages in Irradiated Chicken Embryos. - Rheinecker, Renee (Missouri Southern State University (Joplin, Mo.), 2013)
Abstract: The objective of this experiment is to quantify the amount of chromosomal damage that occurs from using diagnostic x-ray procedures. The range of radiation exposure is increased by approximately 15% starting at 40 kVp and ending at 90 kVp. These numbers are used because they are the upper amounts of diagnostic x-ray exposure and some therapeutic levels, such as CT scans. The degree of chromosomal fragmentation is determined by quantifying DNA repair enzyme activity on whole cell preparations of early chicken embryos.; 1 online resource (11 pages) : illustrations, PDF file